KOMPETENSI PAEDAGOGIK GURU DALAM PENYUSUNAN PERENCANAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DAPAT MENINGKATKAN KUALITAS MENGAJAR GURU DAN HASIL BELAJAR SISWA DI MADRASAH IBTIDAIYAH NEGERI BINJAI SEMESTER GENAP TAHUN PELAJARAN 2021/2022 - Jamilah Jamilah (Universitas Negeri Medan, 2023)
Teacher's Pedagogic Competence in Preparing Learning Planning Through Academic Supervision Can Improve Teacher Teaching Quality and Student Learning Outcomes at Madrasah Ibtidaiyah Negeri Binjai Even Semester 2021/2022 Academic Year. Writing School Action Research (PTS) was carried out by researchers on 15 educators (teachers) consisting of 2 cycles by applying Teacher's Paedagogic Competence in Preparing Learning Planning Through Academic Supervision Can Improve the Quality of Teaching Teachers at Madrasah Ibtidaiyah Negeri Binjai Even Semester of Academic Year 2021/2022, this can be seen from the results of the calculation of the first cycle for the second cycle with a validity value of 0.727 (Teacher Learning Planning Ability) and 0.771 (Learning Planning Components), as well as a t-test value of 3.959 (Teacher Learning Planning Ability) and equal to 4.53 (Learning Planning Components). As well as Teacher Paedagogic Competence in Preparing Learning Planning Through Academic Supervision Can Improve Student Learning Outcomes at Madrasah Ibtidaiyah Negeri Binjai Even Semester 2021/2022 Academic Year, this can be seen from the results of calculating the average value of 15 subjects in the first cycle to the second cycle with the validity value is 0.784, and the t-test value is 4.732. All calculation results show a significant value.